STUDY OF THE EFFECT OF COMPRESSIVE FORCES ON THE MECHANICAL PROPERTIES OF A CERAMIC BY SPECKLE PHOTOGRAPHY - Belabbas, Fadila; Seghiri, Sena (university of M'sila, 2021)
The main objective of this research is to study the mechanical properties of ceramics, from which we took kaolin (KT2) as an example. We used a new optical technique called speckle photography to qualitatively exploit the compressive behaviour of ceramics. This method also allows us to visualize the deformation fields of the ceramic under compression on all the surface of the sample and the probable defects during manufacture.